SYNTHESIS, STRUCTURE CHARACTERIZATION, SEEBECK COEFFICIENT, AND AC CONDUCTIVITY OF PEROVSKITE COMPOUND EUFEO3 - Mohammad Rahman, Raihan
EuFeO3 compound is one of the family of RFeO3 (rare earth orthoferrite) which has a perovskite crystal structure. RFeO3 compounds are antiferromagnetic with Néel temperatures ranging from 620 K for LuFeO3 to 740 K for LaFeO3. The increase in the Néel temperature corresponds to a change in the radius of the larger R ion and is associated with an increase in the bond angle between Fe-O-Fe in the octahedral plane. EuFeO3 is predicted by theoretical studies to have a fairly high Seebeck coefficient by Rajan et al. (J. Appl. Phys. 128, 155101 (2020)) reached 1000 ????V/K. This final project is intended to validate these predictions. Seebeck coefficient measurements were carried out on single-phase EuFeO3 samples synthesized using the sol-gel method. The results of crystal structure analysis using the GSAS-II program to get lattice constants and bond angles, each of which is a = 5.37295 ?, b = 5.59730 ?, c = 7.68670 ?, and Fe-O2-Fe is 147, 9498°. The value of the Seebeck coefficient measured exceed 10000 ????V/K (12517 ????V/K at a temperature of 462 K) with the condition of the sample that has undergone a color change from the initial orange-red to grayish. The limitation of the measurement is also caused by the very high value of dc resistivity at room temperature. To determine the electrical transport properties of EuFeO3, capacitance measurements were carried out in the frequency and temperature ranges, respectively at 500 Hz to 2 Mhz and at 145 K to 300 K. The results of these measurements were then converted into ac conductivity and based on the frequency power law model, ????????, indicates that the conduction mechanism is dominated by localized hopping (????>1).